Synthesis of sorbitol fatty acid ester through esterification of sorbitol with azelaic acid catalysed by germanium (IV) oxide - Nurwadiah, Azizan (2017)
Conventionally, polyurethane (PU) is derived from polyester polyol from non-renewable resource which is petroleum feedstock. As an alternative for the current resource, bio-based polyester polyol is introduced. In this study, bio-based reactants which are sorbitol and azelaic acid will be used to produce bio-based polyester polyol. Both of the reactants are derived from renewable resources. Sorbitol, C6H14O6 is a type of polyol with six hydroxyl group which derived from fruits, corn and seaweed, while azelaic acid, C9H16O4 is a dicarboxylic acid and it is found in rye, wheat and barley. Germanium (IV) oxide is a type of heterogeneous acid catalyst and it is chosen because to eliminate the use of homogeneous acid catalyst which is difficult in term of separation for reuse propose. This study is focusing on the identification of best operating condition for reaction. The operating parameters include reaction temperature, molar ratio and catalyst loading. The reaction temperature is in range of 160˚C to 220˚C. The molar ratio of sorbitol and azelaic acid are varied from 1:1, 2:1, 3:1 and 4:1. The catalyst loading is in range of 1 vol % of azelaic acid to 4 vol % of azelaic acid. The best operating conditions for this study are reaction temperature of 200˚C, molar ratio of 4:1 (SB:AA) and catalyst loading of 3 vol % of azelaic acid. The samples were analysed using gas chromatography (GC) with split injector, flame ionization detector fitted with a glass CP-TAP CB column. From GC analysis, presence of isosorbide was detected which derived from anhydrization of sorbitol.